Endemic infections of bovine viral diarrhea virus genotypes 1b and 2a isolated from cattle in Japan between 2014 and 2020 - NISHIMORI, Asami; HIROSE, Shizuka; OGINO, Saho; ANDOH, Kiyohiko; ISODA, Norikazu; SAKODA, Yoshihiro (Journal of Veterinary Medical Science, 2022)
Bovine viral diarrhea virus (BVDV) is a causative agent of bovine viral diarrhea. In Japan, a previous study reported that subgenotype 1b viruses were predominant until 2014. Because there is little information regarding the recent epidemiological status of BVDV circulating in Japan, we performed genetic characterization of 909 BVDV isolates obtained between 2014 and 2020. We found that 657 and 252 isolates were classified as BVDV-1 and BVDV-2, respectively, and that they were further subdivided into 1a (35 isolates, 3.9%), 1b (588, 64.7%), 1c (34, 3.7%), and 2a (252, 27.7%). Phylogenetic analysis using entire E2 coding sequence revealed that a major domestic cluster in Japan among BVDV-1b and 2a viruses were unchanged from a previous study conducted from 2006 to 2014. These results provide updated information concerning the epidemic strain of BVDV in Japan, which would be helpful for appropriate vaccine selection.